Degradação ambiental em área de preservação permanente do Igarapé Carrapato em Boa Vista/RR: reflexos decorrentes dos usos múltiplos da água - Nobre, Leuda Martins (Universidade Federal de Roraima, 2024)
The Law 12. 651/2012 defined Areas of Permanent Preservation (APPs) as protected areas, with or without vegetation, with the environmental function of preserving natural resources, biodiversity, the gene flow of fauna and flora, the soil and the security of the well-being of populations. The growing occupation within the APPs of watercourses where the environmental impacts resulting from the occupation of these areas have generated several environmental problems such as the decharacterization and loss of their functionalities require analysis of the characteristics of the natural physical environment and of the triggered processes, which justifies the development of this study. The studied area is the Igarapé Carrapato, located in Boa Vista, Roraima, being an affluent’s left bank river of the lower course of the Cauamé River, measuring approximately 18.63 km from its source to its mouth in the rural area of Boa Vista/ RR. The objective was to identify, analyze and map the types of environmental degradations installed in the APPs of Igarapé Carrapato resulting from multiple uses of water. For this study, the methodology of the environmental quality index for APPs (iQ) was used. Several studies indicate that the use of this methodology has proven to be efficient in the survey and assessment of environmental impacts in watercourse’s APPs, which consisted of drawing a circle around the source of Igarapé Carrapato and dividing into quadrants (Q1, Q2 , Q3, Q4) and divide the main course into four sections (T1, T2, T3, T4) of approximately equal size, going from the downstream of the APP boundary, from the spring to its mouth. The environmental impacts, in the quadrants and sections, were identified by the presence or absence of 13 indicators such as aquaculture, agriculture, livestock, exposed soil, civil construction, deforestation, electrical network, solid waste, roads, drainage, bridges, bathing, bus. The iQ describes the preservation state of APPs based on limits of values that adopted the concepts of preserved, disturbed, highly disturbed, degraded and highly degraded. By surveying the multiple uses of water, it was possible to verify that the water resource is being widely used for grain and grass agriculture, aquaculture, livestock and horticulture. The study carried out made it possible to understand the real situation, allowing classifying the permanent preservation area of Igarapé Carrapato as preserved in stretch 1 and quadrants of the spring; disturbed in section 2; highly disturbed in section 3; and degraded in section 4, due to the use of the soil and, consequently, of water. The product of this research was a thematic map of land use and coverage, accompanied by a booklet of good practices for the preservation of APPs, aimed at the school community, the community of Igarapé Carrapato and environmental managers, with the intention of supporting decision making in mitigating actions, as a way to maintain sustainable development in the Igarapé Carrapato basin, preserving its APPs.